KEBIJAKAN HUKUM PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN BANGSA: PEREMPUAN DAN POLITIK - Wirawan, Vani; Rodiah, Ita (Gapenas Publisher, 2024)
The role of women in nation-building, especially in political participation, today is very calculated and greatly influences the development of the ongoing process of government in Indonesia. This study aims to determine legal policies on the protection of women's participation in participating in the implementation of nation building as political participation. The research writing method used is normative legal research with a conceptual approach. The results of the study show that the strengthening of Presidential Instruction Number 9 of 2000 concerning Gender Mainstreaming in National Development needs continuity from all parties. Women activists seem to be more focused and consistent in fighting for a quota of 30% women's representation in politics as a common struggle agenda. At least, in the last decade, we have seen strong developments in various women's struggle efforts from politicians, NGO activists, mass organizations, academics, women journalists, even artists and celebrities